Habitual transience : orientation and disorientation within non-places - Heymans, Simone (Rhodes University, Faculty of Humanities, Department of Fine Art, 2014)
This mini-thesis is a supporting document to the exhibition titled via: a phenomenological site-specific series of intermedia interventions and installations at the 1820 Settlers National Monument in Grahamstown. This mini-thesis examines ways in which one negotiates the movement of the self and interactions with others within the non-place. Non-places are 'habitually transient' spaces for passage, communication and consumption, often viewed from highways, vehicles, hotels, petrol stations, airports and supermarkets. Characteristic of these generic and somewhat homogenous spaces is the paradox of material excess and concurrent psychological lack where a feeling of disorientation and disconnection is established due to the excesses of Supermodernity: excess of the individual, time and space. The non-place is a contested space as it does not hold enough significance to be regarded as a place and yet, despite its banality, is necessary "“ and in many ways a privilege "“ in everyday living. I explore the concept of non-places in relation to the intricate notions of space and place, and draw on empirical research as a means to interrogate how one perceives the phenomenological qualities of one's surroundings. I discuss the implications of the multiplication of the non-place in relation to globalisation, time"“space compression, site-specific art and absentmindedness, as theoretical themes which underpin the practical component of my research. In addition, I situate my artistic practice in relation to other contemporary artists dealing with the non-place as a theme, and critically engage with the multi-disciplinary and sensory installations and video pieces of Belgian artist Hans Op de Beeck.
Keywords: Beeck, Hans Op de, 1969-; Space perception; Place (Philosophy); Liminality; Art and society; Art, Modern -- 21st century; Art, Abstract -- 21st century